Robber flies (Insecta: Diptera: Asilidae) of Wyoming, USA with keys to genera and species - Lavigne, Robert J.; Dennis, D. Steve (Zootaxa, 2019)
There are 171 species of robber flies recorded for Wyoming, USA, including three newly described species (Cyrtopogon hollandi sp. nov., C. martini sp. nov., and Stenopogon graminis sp. nov.) in this paper, in 10 of the 14 recognized subfamilies. The largest numbers of species belong to the Asilinae (61) followed by Brachyrhopalinae (35), Laphriinae (23), Stenopogoninae (19), Dasypogoninae (9), Stichopogoninae (9), Leptogastrinae (8), Dioctriinae (3), Willistonininae (3), and Trigonomiminae (1). The most species (136) occur in one or more of the shrub/grassland vegetation types, with fewer species occurring in the grassland vegetation types (130), the forest (78 species) and in the shrub (24 species) vegetation types. Keys to subfamilies, genera and species with brief species descriptions are provided; the ecology and ethology of individual species are discussed.